How do creative practitioners use talk to create an environment for learning? - Hadaway, Sophie (2024)
Schools in Wales are increasingly engaging creative practitioners to work alongside teachers. This in situ professional development aims to develop creative learning approaches across subject disciplines and phases. There is a substantive amount of research focusing on the practice of creative practitioners working in schools, some of which mentions the differences between teacher and artist interactions. There is also a separate well-evidenced body of research both nationally and internationally highlighting the importance and impact of effective teacher-pupil dialogue within the classroom and its accompanying impact on learning. The body of research concerning dialogue within the classroom has been directly focused on teachers and their interactions with their students and on student-to-student interaction. There is little in-depth or specific focus on creative practitioners’ use of talk or dialogic approach when working with children. My research aimed to study and analyse the dialogic approaches of creative practitioners and to consider how this contributes to creating a productive environment for learning. My research investigated the practice of five artists working in three primary schools in Wales focusing specifically and in detail on their use of talk. My aim was to draw out the elements of the dialogic approach of a visual artist, two sculptors, a ceramicist and a filmmaker when working in three schools, documented through observation, film and interview. I considered how the creative practitioners used talk to generate an environment for learning by showing that these creative practitioners initiated and engaged in ongoing conversations with the children from the lesson outset. I noted their ways of questioning, stemming from a genuine interest and purpose in hearing the children's ideas and thoughts. Listening was illuminated as an important element – attentive and acute and without judgement. The creative practitioners adopted multiple means of enabling the children to engage with their ideas and thoughts through play, experimentation and the abstraction of ideas - encouraging inter-pupil dialogue. Finally, my analysis showed that the creative practitioners developed a sense of collective endeavour where every child was valued and integral to the purpose and direction of the learning. I conclude that these findings offer new knowledge into how creative practitioners skilfully use talk to engage and involve children in their learning. This research thus provides insights for teachers and creative practitioners interested in developing a dialogic pedagogy and has the potential to remind educational decision makers and policy makers of the educational value that creative practitioners bring when working in schools.